The Dirty Dozen pesticides to bite the dust - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Over 100 governments met in Montreal (Canada) at the end of June for the first round of talks on an international agreement to minimise emissions and releases of Persistent Organic Polluters (POPs) such as DDT and other members of 'The Dirty Dozen'...